Modelo de negocio para la comercialización de helados cremosos frutales de heladería Ricky en el sector sur de Guayaquil - Álava Bastidas, Valeria Samanta (2023)
Ricky's Ice Cream is a business that develops a production line of creamy fruit ice cream that meets people's needs for its high nutritional value. For this, a business model is proposed for commercialization in the city of Guayaquil, under the name of simplified joint stock company. The target market to which the business plan is directed is basically the general public. Among the objectives of this project are to design a business model for Ricky’s Ice Cream that allows the elaboration and commercialization of creamy fruit ice creams; explain the theoretical references that support the research, make a financial plan model for Ricky's Ice Cream Shop. To achieve the proposed objectives, various commercial and administrative strategies are implemented for customer loyalty. Ricky's ice cream parlor considers hiring six positions for its organization chart: a manager, a purchase manager, an accountant, an ice cream production assistant, a cashier, and a salesperson. Most of the positions will be full-time, with the exception of an accountant who will be involved in service delivery, as the volume of transactions does not justify fulltime employment. For the methodological framework, three important methods were used: the theoretical method, the inductive-deductive method and the analytical-synthetic method. For the financial analysis, cash inflows and outflows were taken into account, that is, the net profit of the first year was taken as input.